Harcèlement moral et sexuel. Stratégies d’adaptation et conséquences sur la santé des travailleurs et des travailleuses - Ada Garcia; Bernard Hacourt; Virginie Bara (Perspectives Interdisciplinaires sur le Travail et la Santé)
Over the last few years, attention has been focused on the issue of workplace violence, as witnessed by the recently published work on moral harassment. In Belgium, the results of a national survey "Violence in the Workplace. Moral and Sexual Harassment : Consequences for Female and Male Workers" showed that moral and sexual harassment is a veritable societal problem, not only due to its extent, but also its devastating negative impact on the physical and mental health of male and female workers. The aim of this article is to summarize the main negative consequences and suffering endured by victims in their daily lives. The article also highlights the individual strategies adopted by female and male victims of violence in the workplace and underscores the importance of understanding the phenomenon from a gender standpoint.